Every single second - Springstubb, Tricia (Balzer + Bray, an imprint of HarperCollinsPublishers, 2016)
Twelve-year-old Nella Sabatini's life is changing too soon, too fast. Her best friend, Clem, doesn't seem concerned; she's busy figuring out the best way to spend the "leap second" -- an extra second about to be added to the world's official clock. The only person who might understand how Nella feels is Angela, but the two of them have gone from being "secret sisters" to not talking at all. Then Angela's idolized big brother makes a terrible, fatal mistake, one that tears apart their tight-knit community and plunges his family into a whirlwind of harsh publicity and judgment. In the midst of this controversy, Nella is faced with a series of startling revelations about her parents, friends, and neighborhood. As Angela's situation becomes dangerous, Nella must choose whether to stand by or stand up.